Welsh Women's Industrial Fiction 1880–1910. Issue 4 (2nd October 2017) - Bohata, Kirsti; Jones, Alexandra
ABSTRACT: From the beginning of the genre, women writers have made a major contribution to the development of industrial writing. Although prevented from gaining first-hand experience of the coalface, Welsh women writers were amongst the first to try to fictionalize those heavy industries—coal and metal in the south, and slate in the north—which dominated the lives of the majority of the late nineteenth-century Welsh population. Treatment of industrial matter is generally fragmentary in this early women's writing; industrial imagery and metaphor may be used in novels that are not primarily "about" industry at all. Yet from c. 1880–1910, Welsh women writers made a significant—and hitherto critically neglected—attempt to make sense in literature of contemporary industrial Wales in powerful and innovative ways. This essay maps their contribution and considers anglophone Welsh women writers' adaptations and innovations of form (particularly romance) as they try to find a way of representing industrial landscapes, communities and the daily realities of industrial labour. It identifies the genesis in women's writing of tropes that would become central to later industrial fiction, including depictions of industrial accident, injury, death and disability. And it explores the representation of social relations (class, gender, ethnicity, sexuality) and conflict on this tumultuous, dangerous new stage.